2018
DOI: 10.1175/bams-d-16-0162.1
|View full text |Cite
|
Sign up to set email alerts
|

The Environment Canada Pan and Parapan American Science Showcase Project

Abstract: The Pan and Parapan American Games (PA15) are the third largest sporting event in the world and were held in Toronto in the summer of 2015 (10–26 July and 7–15 August). This was used as an opportunity to coordinate and showcase existing innovative research and development activities related to weather, air quality (AQ), and health at Environment and Climate Change Canada. New observational technologies included weather stations based on compact sensors that were augmented with black globe thermometers, two Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…Doppler lidars provide precise and accurate backscatter and Doppler velocity measurements at high temporal-and spatial-resolution along the lidar beam's path (radial direction). As such, they have demonstrated the ability to measure fast-evolving meteorological features, such as lake breezes and low-level jets, and cloud microphysical properties [7,[26][27][28][29].…”
Section: Doppler Light Detection and Ranging (Lidar)mentioning
confidence: 99%
“…Doppler lidars provide precise and accurate backscatter and Doppler velocity measurements at high temporal-and spatial-resolution along the lidar beam's path (radial direction). As such, they have demonstrated the ability to measure fast-evolving meteorological features, such as lake breezes and low-level jets, and cloud microphysical properties [7,[26][27][28][29].…”
Section: Doppler Light Detection and Ranging (Lidar)mentioning
confidence: 99%
“…CRUISER was deployed during two seasons over the Greater Toronto Area (GTA), a metropolitan area encompassing the city of Toronto and four regional municipalities with a population of over 6 million. The summer campaign took place over 9 days in July 2015 (15,16,17,20,21,22,23,27, and 28 July) as part of the Environment Canada Pan and Parapan American Science Showcase (ECPASS) (Joe et al, 2018). The winter campaign took place over 8 days in January 2016 (11,13,14,15,18,19,20, and 21 January) as part of a health exposure mapping study.…”
Section: Overview Of Mobile Measurementsmentioning
confidence: 99%
“…Volatile organic compounds were measured using a protontransfer-reaction time-of-flight mass spectrometer (PTR-TOF-8000, Ionicon Analytik). The operating principles of the PTR-TOF-MS instrument have been described elsewhere (Jordan et al, 2009;Li et al, 2017); further details can be found in the Supplement. Briefly, the PTR-TOF-MS was operated with an E / N value of 140 Td.…”
Section: Proton-transfer-reaction Time-of-flight Mass Spectrometry (Pmentioning
confidence: 99%
“…Similarly, studies quantifying emissions in which the vehicle stops to obtain wind measurements (Brantley et al, 2014) and the anemometer is placed ahead of and above the vehicle are unlikely to require compensations for the vehicle's flow field. Vehicles outfitted to study severe weather (Curry et al, 2017;Taylor et al, 2011) and urban meteorology (Joe et al, 2018) show resilience to bias by also outfitting vehicles with wind sensors above and ahead of the vehicle. Vehicle-based anemometer measurements should be calibrated for vehicle shape and anemometer placement, but as this can be costly and time-consuming truck-based anemometers should be placed as far forward and as high as possible to obtain the most accurate results.…”
Section: Discussionmentioning
confidence: 99%